Carte Nouvelle de l'Amerique Angloise Contenant La Virginie, Mary-land, Caroline, Pensylvania, Nouvelle Iorck. N: Iarsey, N: France, et Les Terres Nouvellement Decouerte. - Sanson. (Mortier, Pierre., 1700)
Eastern North America. Copied from Morden-Brown ca. 1695. An untitled inset at the left shows Boston Harbor and serves to hide some of the unknown western regions. Some illustrated topography shows towns, river systems, individual trees to indicate forests and some banks off the coast of Nova Scotia and Newfoundland. Relief shown pictorially. Small compass rose on upper right corner.